CLUSTER DEVELOPMENT IN UZBEKISTAN’S ECONOMY: PRODUCTION VOLUME, INVESTMENT FLOWS, AND EXPORT DYNAMICS (2022–2024) (American Journal of Business Management, Economics and Banking, 2025)
This article analyzes the formation and development of the clustering process in the economy of Uzbekistan. Although the cluster system is relatively new, it plays an important role in attracting investments, expanding production volumes, and increasing export potential. The purpose of the study is to study the dynamics of production, investment, and export indicators of clusters. Statistics for 2022-2024 showed that cluster production volumes are growing steadily, investments are modernizing infrastructure, and export indicators are increasing competitiveness in international markets. The results confirm the formation of the cluster system as a modern production model in the economy of Uzbekistan.